IMPLEMENTASI KEBIJAKAN PELAYANAN KESEJAHTERAAN LANSIA DI KABUPATEN MOROWALI - Samsul Alam (Jurnal Administrasi Negara dan Ilmu Pemerintahan, 2023)
This study aims to implement policies for elderly welfare services in Morowali district. The research method used is a qualitative descriptive method and data collection techniques by means of observation, interviews and documentation. Selection of 5 informants using a purposive technique by following the procedure, namely data reduction, data exposure and drawing conclusions (verification). The guideline is socializing the police and the mechanisms for implementing the elderly wafare service resources, the availability of both human resources and resources in the form of physical facilities (facilities and infrastructure) is very influential in the successful implementation of the elderly welfare service policy. This resource indicator cannot be said to be ineffective, especially in relation to honorarium. The disposition/attitude of the implementer, the attitude of the implementer of the Elderly Welfare service policy is very good, especially for the elderly companion because even though they do not get an honorarium or wages for what they do, they still carry out the tasks given voluntarily and voluntarily. with an open heart. The bureaucratic structure that refers to the Standard Operating Procedure (SOP) in the Implementation of Elderly Welfare Service Policies in Morowali Regency is quite well implemented according to the applicable policy rules even though the facilities and infrastructure are still minimal